Dynamics of Halal Certification Acceleration in 2026: A Juridical Analysis of the Postponement of Mandatory Halal Requirements and the Integrity of the Self-Declaration Scheme for Micro and Small Enterprises (MSEs) - Siti Aminah Najmudin; Siti Adila Nazwa; Atmo Prawiro (Ilomata International Journal of Social Science, 2026)
Pursuant to Article 160 paragraph (2) of Government Regulation No. 42 of 2024 implementing Law No. 33 of 2014 as amended by Law No. 6 of 2023 on Job Creation, the government extended the mandatory halal certification deadline to 17 October 2026 exclusively for micro and small enterprise (MSE) producers of food and beverage products, slaughter products, and slaughtering services; this targeted postponement does not apply to medium and large enterprises or other product categories. This article examines the juridical consistency of the postponement with the principle of legal certainty and the normative robustness of the self-declare scheme in safeguarding halal integrity. Adopting a normative legal research design based on statutory and conceptual approaches, the study analyzes primary legal instruments and secondary materials for doctrinal analysis. The analysis demonstrates that the postponement reflects a policy-based interpretation accommodating structural constraints such as limited administrative capacity, institutional readiness, and MSE compliance challenges, rather than a deviation from the mandatory halal certification regime. Nevertheless, the self-declare mechanism, grounded in Article 4A of the Job Creation Law, raises concerns regarding substantive verification adequacy and institutional oversight. In addition, interpretative ambiguities within implementing provisions on transitional periods and supervisory mechanisms generate potential legal uncertainty. The principal implication highlights the need to strengthen supervisory and verification mechanisms by optimizing Halal Product Process Assistants (P3H) roles and ensuring SiHalal system coherence, so that the postponement serves as a justified transitional measure rather than diluting halal assurance standards.